Quantitative Determination of Iron-Siderophore Complexes in Peat by Isotope-Exchange Size-Exclusion UPLC-Electrospray Ionization High-Resolution Accurate Mass (HRAM) Mass Spectrometry - Maknun L. (2023)
A method was developed for the quantification of iron-siderophore complexes by electrospray high-resolution accurate mass (HRAM) mass spectrometry (MS) without the need for authentic standards. The bulk of iron-siderophore complexes was purified by solid-phase extraction (SPE) and concentrated by evaporation. The individual complexes were identified by fast size-exclusion chromatography (FastSEC)-Orbitrap MSn on the basis of the exact molecular mass (±1 ppm) and MS2 or MS3 fragmentation. Their capability to readily exchange the natural 56Fe for the added 58Fe was demonstrated by SEC with ICP MS and ESI MS detection. The method was applied to the analysis of peat sampled in the eastern part of the French Pyrenean mountains. Nineteen siderophores belonging to four different classes were identified and quantified. The results were validated using ICP MS detection of iron by matching the sum of iron complexes determined by isotope exchange-ESI MS within each peak observed by FastSEC-ICP MS.